2020
DOI: 10.1108/nfs-01-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive and behavioral impact of a culinary education program on schoolchildren

Abstract: Purpose The purpose of this paper is to design a culinary education program and ascertain its impact on knowledge, phobias, culinary skills and diet quality in schoolchildren. Design/methodology/approach Repeated measures design to determine changes after the implementation of the culinary education program in a pre-school and primary school located in a Madrid (Spain) neighborhood with a low socioeconomic level. A total of 58 children agreed to participate in the program and 40 parents authorized the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A high‐level overview of the characteristics and key components of interest of the 38 studies can be found in Table 2. The majority of studies ( n = 25) were conducted in North America (Adedokun et al, 2020; Auld et al, 1998; Bisset et al, 2008; Chen et al, 2014; Cullen et al, 2007; Cunningham‐Sabo & Lohse, 2013, 2014; DeJesus et al, 2019; Ehrenberg et al, 2019; Gutschall & Settle, 2013; Harley et al, 2018; Harmon et al, 2015; Heerman et al, 2021; Isoldi & Dolar, 2016, 2020; Isoldi et al, 2014; Jacob et al, 2019; Jarpe‐Ratner et al, 2016; Liquori et al, 1998; Moore et al, 2020; Overcash et al, 2018; Quinn et al, 2003; Saha et al, 2020; Saxe‐Custack et al, 2021; Zahr & Sibeko, 2017), followed by 10 conducted in Europe (Al Ali et al, 2020; Allirot et al, 2016; Battjes‐Fries et al, 2017; Caraher et al, 2013; Dean et al, 2022; Elsborg et al, 2022; Ensaff et al, 2017; Højer et al, 2021; Maiz et al, 2021; Van der Horst et al, 2014), two in Asia (Bai et al, 2018; Yoshii et al, 2021) and one in Australia (Ritchie et al, 2015). The publication dates ranged from 1998 (Auld et al, 1998; Liquori et al, 1998) to 2022 (Elsborg et al, 2022), with 87% of identified studies published in the last 10 years and 55% published in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high‐level overview of the characteristics and key components of interest of the 38 studies can be found in Table 2. The majority of studies ( n = 25) were conducted in North America (Adedokun et al, 2020; Auld et al, 1998; Bisset et al, 2008; Chen et al, 2014; Cullen et al, 2007; Cunningham‐Sabo & Lohse, 2013, 2014; DeJesus et al, 2019; Ehrenberg et al, 2019; Gutschall & Settle, 2013; Harley et al, 2018; Harmon et al, 2015; Heerman et al, 2021; Isoldi & Dolar, 2016, 2020; Isoldi et al, 2014; Jacob et al, 2019; Jarpe‐Ratner et al, 2016; Liquori et al, 1998; Moore et al, 2020; Overcash et al, 2018; Quinn et al, 2003; Saha et al, 2020; Saxe‐Custack et al, 2021; Zahr & Sibeko, 2017), followed by 10 conducted in Europe (Al Ali et al, 2020; Allirot et al, 2016; Battjes‐Fries et al, 2017; Caraher et al, 2013; Dean et al, 2022; Elsborg et al, 2022; Ensaff et al, 2017; Højer et al, 2021; Maiz et al, 2021; Van der Horst et al, 2014), two in Asia (Bai et al, 2018; Yoshii et al, 2021) and one in Australia (Ritchie et al, 2015). The publication dates ranged from 1998 (Auld et al, 1998; Liquori et al, 1998) to 2022 (Elsborg et al, 2022), with 87% of identified studies published in the last 10 years and 55% published in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to study design, 22 of the included studies had a single or multiple control or comparison groups, including one study that had a post‐test‐only control (Quinn et al, 2003), and one that had a pre‐test‐only control (Chen et al, 2014). Study designs included RCTs ( n = 2; Cunningham‐Sabo & Lohse, 2013; Jacob et al, 2019), two‐group or multi‐group pre‐ and post‐test ( n = 16; Allirot et al, 2016; Auld et al, 1998; Bai et al, 2018; Battjes‐Fries et al, 2017; Caraher et al, 2013; Cunningham‐Sabo & Lohse, 2014; Dean et al, 2022; Elsborg et al, 2022; Ensaff et al, 2017; Harley et al, 2018; Højer et al, 2021; Liquori et al, 1998; Maiz et al, 2021; Moore et al, 2020; Yoshii et al, 2021; Zahr & Sibeko, 2017), single‐group pre‐ and post‐test ( n = 15; Adedokun et al, 2020; Al Ali et al, 2020; Cullen et al, 2007; Ehrenberg et al, 2019; Gutschall & Settle, 2013; Harmon et al, 2015; Heerman et al, 2021; Isoldi & Dolar, 2016, 2020; Isoldi et al, 2014; Jarpe‐Ratner et al, 2016; Overcash et al, 2018; Ritchie et al, 2015; Saha et al, 2020; Saxe‐Custack et al, 2021), between and/or within subject ( n = 3; Allirot et al, 2016; DeJesus et al, 2019; Van der Horst et al, 2014) and a mixed design ( n = 2; Chen et al, 2014; Quinn et al, 2003). Sample sizes ranged from 17 (Ehrenberg et al, 2019) to 1204 (Chen et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, food education interventions are beginning to combine practical-based growing and cooking with knowledge-based nutrition [ 38 ]. For example, a systematic review examined the impact of garden-based nutrition programmes on children‘s nutritional outcomes [ 40 ], but more research into comprehensive food education is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, studies do combine two topics like cooking and healthy eating, or growing fruit and vegetables and cooking [ 38 , 39 ]. A systematic review examining garden-based nutrition programmes for their impact on children’s nutritional outcomes found, despite scant evidence, that such programmes have potential to influence children’s fruit and vegetable consumption [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…As many children and adolescents grow and develop in obesogenic environments that promote high caloric intake and physical inactivity (Bejarano et al , 2021), educational settings provided by schools may become suitable environments for promoting the adoption of healthier food consumption habits (Al Ali et al , 2020). Interventions targeted towards these goals may be carried out at schools, as consumption patterns and food preferences are developed at an early age and can last well into adulthood (Hawkes et al , 2015; Heelan et al , 2015; Mohajeri et al , 2022; Welker et al , 2016).…”
Section: Introductionmentioning
confidence: 99%